(untitled) (Journal of Educational Sciences, 2017)
The article provides an analysis of the current work, exploring issues of perception and understanding of the foreign text. The purpose of this article is to show the correlation of linguistic and psychological categories in the process of perception and understanding of foreign-language text as an object of intercultural communication, to generalize theoretical knowledge and practical experience in the teaching of reading foreign-language text , in particular in the Russian language. A brief overview of learning styles of students, which enables the teacher to plan more effectively the work for the class and the student to improve motivation and more effective learning. Special attention is paid to obstacles to understanding foreign language text and the absorption, as lexico-grammatical and cultural material. The authors generalized the theoretical material on some aspects of the methods of teaching reading in a foreign language, offers their own approach to solve methodical tasks. In this article attention is drawn not to the use of specific exercises, but on problems, with what readers can meet and offers their own vision of the reasons of their occurrence and solutions. Key words: Russian as a foreign language (RFL), foreign language, psychological problems of perception and comprehension, kinds of reading, reading strategies, learning styles.